2014
DOI: 10.1097/aog.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Delivery After Successful External Cephalic Version

Abstract: Women who have had a successful external cephalic version for breech presentation are at increased risk for cesarean delivery and instrumental vaginal delivery as compared with women with a spontaneous cephalic presentation. Nevertheless, with a number needed to treat of three, external cephalic version still remains a very efficient procedure to prevent a cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…Due to the data structure, the study population was derived by combining: [1] women who had a record of ECV at ≥36 weeks during pregnancy, and [2] breech-presenting singleton infants born at ≥36 weeks, taken from birth records (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the data structure, the study population was derived by combining: [1] women who had a record of ECV at ≥36 weeks during pregnancy, and [2] breech-presenting singleton infants born at ≥36 weeks, taken from birth records (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…1). To examine the uptake of ECV, the population of breech pregnancies were classified retrospectively into 3 groups: [1] women with ECV, [2] women potentially eligible for ECV, and [3] women considered ineligible for ECV.
Fig. 1Selection of study population from available records and definition of the study groups.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A large meta-analysis of 46,641 patients found an increased risk for cesarean section after successful ECV with an OR of 2.2, and likewise increased risks for dystocia, fetal distress, and instrumental vaginal delivery. Nevertheless, the authors concluded that ECV is a very efficient procedure, as the number needed to prevent a cesarean section was only 3 [10]. Another meta-analysis similarly found the C/S rate after successful ECV to be 2 times as high as after spontaneous cephalic-presenting pregnancies [11].…”
Section: Discussionmentioning
confidence: 90%
“…s 3,1 poskusa ZO enemu carskemu rezu. Zmanjšanje števila carskih rezov kaže reProDukcIJa človeka večina raziskav s tega področja (31)(32)(33)(34). Potrdila ga je zadnja Cochraneova raziskava Hofmeyrja in sodelavcev (12).…”
Section: Razpravljanjeunclassified